2011
DOI: 10.1093/rheumatology/ker178
|View full text |Cite
|
Sign up to set email alerts
|

Knocking out of CD38 accelerates development of a lupus-like disease in lpr mice

Abstract: Although the role of CD38 in tolerance is still to be elucidated, we provide evidence that it may play an active role in the control of a murine lupus-like disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Our data showed that CD38 − / − mice presented glomerular thickening, mesangial proliferation and tubular occlusion at 16 months of age (Figure B‐C). These findings correlate with previous reports from CD38 − / − mice backcrossed with a susceptible genetic background that developed a lupus‐like disease, and those Cd38 −/− ‐Fas lpr /Fas lpr presented severe glomerulonephritis and deposition of immune complexes at 6 months of age . Considering these results, we propose that CD38 could play a role in the control of the autoimmune development and autoantibody production.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data showed that CD38 − / − mice presented glomerular thickening, mesangial proliferation and tubular occlusion at 16 months of age (Figure B‐C). These findings correlate with previous reports from CD38 − / − mice backcrossed with a susceptible genetic background that developed a lupus‐like disease, and those Cd38 −/− ‐Fas lpr /Fas lpr presented severe glomerulonephritis and deposition of immune complexes at 6 months of age . Considering these results, we propose that CD38 could play a role in the control of the autoimmune development and autoantibody production.…”
Section: Discussionsupporting
confidence: 91%
“…We evaluated the presence of anti‐dsDNA and ANAs autoantibodies in CD38 − / − mice at 4, 6, 8, 10, 12, 14 and 16 months of age, and no significant differences in the levels of anti‐dsDNA antibodies were observed in CD38 − / − mice from 4 to 10 months old (Figure B). These results correlate with previous reports for CD38 − / − mice in a genetic background susceptible to develop a lupus‐like disease, in which it is reported that there is no increase in anti‐dsDNA antibodies at 6 months of age . Interestingly, after the 12th month, CD38 − / − mice showed an increase in the levels of anti‐dsDNA, which was more evident at 14 and 16 months of age (Figure B‐C).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although CD38 has been used extensively to classify various subpopulations of lymphocytes, in recent years, several publications also have linked CD38 with different pathologies, including autoimmune diseases. Indeed, apoptotic effect mediated by CD38 in immature cells is well described and absence of CD38 in lpr mice has been associated with an accelerated development of a lupus-like disease [17]. Furthermore, an increased acquisition of CD38 expression on memory B cells along with the expansion of plasmablasts observed in active SLE patients further supports the hypothesis of a stronger stimulation on SLE B cells and the subsequent generation of plasmablasts in active disease.…”
Section: Discussionmentioning
confidence: 77%